2020
DOI: 10.1111/joor.12977
|View full text |Cite
|
Sign up to set email alerts
|

Daytime changes of salivary biomarkers involved in pain

Abstract: The study aimed to investigate salivary levels of nerve growth factor (NGF), brain‐derived neurotrophic factor (BDNF), substance P (SP) and glutamate at five time points from morning to afternoon in a well‐characterised healthy and pain‐free individuals. Ten young adults were included. Unstimulated and stimulated whole saliva were collected from each participant repeatedly across the day. Blood samples were drawn in connection with the first and last saliva sample as reference standard. Levels of NGF and BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
9
0
2
Order By: Relevance
“…We have previously shown that BDNF levels are lower in stimulated whole saliva compared to resting whole saliva, and consequently the salivary BDNF are affected by the flow rate. One may therefore speculate if the lower levels in patients could be a consequence of the slightly lower flow rate (Table 1) [49]. Plasma BDNF levels on the other hand, showed as expected higher levels in TMDmyalgia.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We have previously shown that BDNF levels are lower in stimulated whole saliva compared to resting whole saliva, and consequently the salivary BDNF are affected by the flow rate. One may therefore speculate if the lower levels in patients could be a consequence of the slightly lower flow rate (Table 1) [49]. Plasma BDNF levels on the other hand, showed as expected higher levels in TMDmyalgia.…”
Section: Discussionmentioning
confidence: 60%
“…Several substances enter the salivary gland from the blood by passing through the intercellular spaces by transcellular or paracellular diffusion, consequently saliva is often regarded as an ultrafiltrate of plasma and contains fractions of proteins derived from the blood stream [42,49], which explains the usually lower concentration of NGF, BDNF and SP in saliva compared to plasma. Glutamate on the contrary showed higher levels in saliva, which imply a local secretion or even a diffusion from adjacent structures e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Por isso, observa-se um interesse crescente no diagnóstico salivar, visto que as glândulas salivares estão integradas ao sistema neuroendócrino e contêm uma grande variedade de moléculas que podem desempenhar papéis importantes na fisiopatologia da dor. (39,40) Muitos constituintes do plasma entram na saliva por difusão passiva, transporte ativo ou ultrafiltração extracelular. (41) Como resultado, a maioria das substâncias encontradas no sangue também estão presentes na saliva e, dessa forma, considera-se a saliva como funcionalmente equivalente ao soro, refletindo o estado fisiológico do organismo.…”
Section: Discussionunclassified
“…However, pain intensity itself may not be a reliable tool for assessing pain, especially for pain in the orofacial region [ 42 , 43 ], since other factors seems to play an important role in the individual’s perception of the pain experience [ 44 ]. Several studies have shown that subjective pain level poorly correlate to several biomarkers shown to be related to pain [ 26 , 45 , 46 , 47 ], but rather to different variables such as physical and psychological functioning [ 42 , 43 , 48 , 49 , 50 ]. Therefore, the multidimensional experience of pain [ 51 ], including not only intensity, but also the cognitive and affective component, should be taken into consideration in further studies [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saliva samples offer a non-invasive method in contrast to other sampling methods, e.g., blood or cerebrospinal fluid. These procedures might also be accompanied by anxiety or pain, which are stressors themselves [ 25 , 26 , 27 ]. Despite the advantages, there are a few drawbacks that need to be considered.…”
Section: Introductionmentioning
confidence: 99%